2012
DOI: 10.1186/1297-9716-43-74
|View full text |Cite
|
Sign up to set email alerts
|

The successful experimental induction of necrotic enteritis in chickens by Clostridium perfringens: a critical review

Abstract: Necrotic enteritis (NE) is one of the most important enteric diseases in poultry and is a high cost to the industry worldwide. It is caused by avian-specific, Necrotic Enteritis Beta toxin (NetB)-producing, strains of Clostridium perfringens that also possess in common other virulence-associated genes. In Europe the disease incidence has increased since the ban on in-feed “growth promoting” antibiotics. Because of this, many recent studies of NE have focused on finding different ways to control the disease, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
282
3
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(298 citation statements)
references
References 84 publications
5
282
3
8
Order By: Relevance
“…It is observed that the severity of the challenge, the infection model, feed and housing conditions of the birds, the strain used for infection, and many more factors affect the protection conferred by a vaccine that is under development. In this regard, a universal infection model that can be used to test the efficacy of vaccines could be of value, as suggested by Shojadoost et al (2012), but this will be difficult to establish. The ideal vaccine strain would be one that, apart from inducing immunity and protection, can be added to the feed or drinking water, or sprayed on the 1-day- CFU, colony-forming units; DEAE-dextran, diethylaminoethanol; EF-Tu, elongation factor Tu; GDP, glyceraldehyde-3-phosphate dehydrogenase; i.m., intramuscular; rPLC, recombinant alpha toxin C-terminal domain-encoding sequence; s.c., subcutaneous; TCP, total combining power; tPFOR, truncated pyruvate:ferredoxin oxidoreductase.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…It is observed that the severity of the challenge, the infection model, feed and housing conditions of the birds, the strain used for infection, and many more factors affect the protection conferred by a vaccine that is under development. In this regard, a universal infection model that can be used to test the efficacy of vaccines could be of value, as suggested by Shojadoost et al (2012), but this will be difficult to establish. The ideal vaccine strain would be one that, apart from inducing immunity and protection, can be added to the feed or drinking water, or sprayed on the 1-day- CFU, colony-forming units; DEAE-dextran, diethylaminoethanol; EF-Tu, elongation factor Tu; GDP, glyceraldehyde-3-phosphate dehydrogenase; i.m., intramuscular; rPLC, recombinant alpha toxin C-terminal domain-encoding sequence; s.c., subcutaneous; TCP, total combining power; tPFOR, truncated pyruvate:ferredoxin oxidoreductase.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…A similar EN disease produced by type A and type C strains affects chickens and other domestic birds. Chicken EN globally costs the poultry industry $2 billion per year (35).…”
mentioning
confidence: 99%
“…Such epithelial damage is permitting the infection by Clostridium perfringens to replicate and produce toxin. Moreover, plasma proteins in the lumen of the gut escaped during coccidiosis are considered favorable nutrient substrates for Clostridium perfringens proliferation and production of toxins (Shojadoost et al, 2012). Finally, it could be concluded that colibacillosis is the most prevalent disease affect different chicken breeds at Alexandria province.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%